Expression of human epidermal growth factor using Ssp DnaB mini-intein as fusion partner in Escherichia coli BL21(DE3) - Yosua Yosua, Rima Melati, Sriwidodo Sriwidodo, Iman Permana Maksum (Journal of Applied Pharmaceutical Science, 2021)
The human epidermal growth factor (hEGF) is widely used clinically as a wound healer, as it has a vital role in stimulating cell proliferation, differentiation, and migration. Consequently, the large-scale production of recombinant hEGF in E. coli has been developed to meet the high demand for hEGF clinically. However, intracellular proteins in E. coli, especially small proteins like hEGF, are degraded by proteases. To overcome this issue, hEGF was fused with CBD-Ssp DnaB to construct a fusion protein CBD-Ssp DnaB-hEGF. This study was conducted to obtain refolded hEGF from the inclusion bodies of CBD-Ssp DnaB-hEGF. The experiment was carried out using E. coli BL21(DE3) containing plasmid pD861-CBD-Ssp DnaB-hEGF. The CBD-Ssp DnaB-hEGF gene was constructed by fusing CBD-Ssp DnaB and hEGF gene and then was optimized. The method was started with E. coli transformation, CBD-Ssp DnaB-hEGF expression, inclusion bodies solubilization, refolding, and simultaneous cleavage to release hEGF. The CBD-Ssp DnaB-hEGF was expressed as inclusion bodies, which can then be purified by washing with Triton X-100 and 1 M urea. The inclusion bodies were solubilized in 8 M urea, the solubilized CBD-Ssp DnaB-hEGF was reformed by dialysis, and then hEGF was spliced by shifting the pH from 8.5 to 6.0 to yield a concentration of 0.163 mg/ml. Therefore, we concluded that hEGF was obtained from the solubilized CBD-Ssp DnaB-hEGF from inclusion bodies produced by E. coli BL21(DE3).
Keywords: Dialysis, E. coli, hEGF, inclusion bodies, Ssp DnaB mini-intein.